Inovasi Kesehatan Terkini Sebagai Strategi Efektif Pada Manajemen Diabetes Di Masa Pandemi: Sebuah Tinjauan Literature - Juwi Athia Rahmini; Dwi Kartika Rahayuningtyas (Poltekkes Kemenkes Jakarta III, 2020)
Diabetics are increasing every year in the world, including in Indonesia. The ministry of health has carried out a solution to control diabetes, but the role of nurses as educators is not yet clearly defined, especially using technological innovations via cell phones or the web. This article aims to describe the development of technological innovations in the perspective of treating diabetes patients based on remote care using cellphone or web technology that can be used in a new adaptation period. The method used is a narrative literature review. Smartphone or web technology offers great benefits for diabetic patient care, behavior modification and education. Interactive Diabetes Diary is proven to help improve this way and is very easy to use. Diabetes management via cell phone or web is one solution for the latest nursing care services in improving the health status of diabetes patients.